Characterising the local immune responses in cervical intraepithelial neoplasia: a cross-sectional and longitudinal analysis - Woo, Y.L.; Sterling, J.; Damay, I.; Coleman, N.; Crawford, R.; Van Der Burg, S.H.; Stanley, M. (Elsevier, 2008)
Introduction: Immunological competence influences the progression of cervical intraepithelial neoplasia (CIN) to invasive cancer. Information on the local immunological changes during the natural course of CIN is central for the development of new therapies.